A flexible family of multi–path routing protocols over a MANET. (18th June 2012) - Rofoee, Bijan Rahimzadeh; Fleury, Martin; Ghanbari, Mohammed; Qadri, Nadia N.
This papers contribution is a family of multi–path routing protocols that emphasise different aspects of multi–path routing, though with a central theme of path reliability within a Mobile Ad Hoc Network (MANET). Tests demonstrate that for all members of the family, the network performance (end–to–end delay and packet loss ratio) compares favorably to the single–path Dynamic Source Routing (DSR) protocol at moderate to high speeds, though there is a trade–off against control packet overhead. Where the design effort differs from other multi–path protocol reviewed is that different aspects of the performance are emphasised in different members of the protocol family.